Revitalizing Merah Putih Village Cooperatives through Maqasid Sharia: A qualitative study of rural economic recovery in Indonesia - Mulyadi, Deni; Arinal Rahmati (Universitas Islam Indonesia, 2026)
IntroductionThe revitalization of village cooperatives has become a strategic priority in Indonesia following the introduction of Presidential Instruction No. 9 of 2025, which promotes the establishment of Merah Putih Village Cooperatives to strengthen rural economic resilience and accelerate national economic recovery. Despite growing interest in cooperative development, limited research has examined how Maqasid Sharia can be systematically integrated into village cooperative governance as a foundation for sustainable, value-based economic empowerment.ObjectivesThis study investigates how the Merah Putih Village Cooperative internalizes the principles of Maqasid Sharia within its institutional structure and governance. It further examines the cooperative’s contribution to improving members’ socioeconomic welfare and evaluates its role in promoting inclusive national economic recovery through a values-driven cooperative model.MethodThis study employed a qualitative research approach combining library research and field research. Data were collected through semi-structured interviews, participant observation, policy document analysis, and an extensive review of scholarly literature. The participants included cooperative managers, members, and local community representatives. The data were analyzed using thematic analysis based on data reduction, data presentation, and conclusion drawing, while source triangulation was applied to enhance the credibility and reliability of the findings.ResultsThe findings demonstrate that the revitalization of the Merah Putih Village Cooperative successfully integrates the five dimensions of Maqasid Sharia into institutional governance and operational practices. The most prominent dimensions are the protection of wealth through transparent financial management and digital bookkeeping, the protection of life through welfare and social assistance programs, and the protection of intellect through Islamic financial literacy initiatives. The cooperative also strengthens the protection of religion through Sharia-compliant governance and the protection of lineage through youth empowerment and intergenerational development programs. Furthermore, the cooperative promotes local entrepreneurship, employment creation, social inclusion, participatory decision-making, and community solidarity while supporting national economic recovery. However, limited digital literacy and technological capacity remain significant challenges to cooperative modernization.ImplicationsThe findings indicate that integrating Maqasid Sharia into village cooperative governance enhances institutional transparency, member participation, social inclusion, and sustainable rural economic development. The study also provides practical guidance for policymakers and cooperative managers in designing value-based governance frameworks that combine ethical principles with digital innovation to strengthen community resilience and national economic recovery.Originality/NoveltyThis study offers one of the first qualitative empirical examinations of the Merah Putih Village Cooperative through the comprehensive lens of Maqasid Sharia. It develops an integrated institutional model that combines Islamic ethical values, participatory governance, digital transformation, and national cooperative policy, extending both institutional theory and the literature on Islamic cooperative governance while providing a practical framework for sustainable village economic revitalization.